KONSEP PENDIDIK DAN PESERTA DIDIK DALAM PERSPEKTIF AL-QUR'AN - Pebi Juliyanti; Nor’ain; Ali Akbar (PT. Hasba Edukasi Mandiri, 2026)
Islamic education positions educators and students as two main components that are interrelated in achieving educational goals. The Qur'an, as the primary source of Islamic teachings, provides guidance on the concepts, roles, duties, and characteristics of educators and students in the educational process. This study aims to examine the concept of educators and students from the perspective of the Qur'an and to identify the duties and characteristics that educators must possess in Islamic education. This study uses a qualitative approach with a library research method. Data were obtained from the Qur'an, hadith, books, scientific journals, and various literature relevant to the research theme. Data collection techniques were carried out through documentation studies, while data analysis used descriptive-analytical content analysis methods. The results of the study indicate that educators from the perspective of the Qur'an do not only function as teachers, but also as guides, role models, moral builders, and developers of students' potential as a whole. Educators have the task of purifying the soul, transforming knowledge, fostering noble morals, and directing students towards a life in accordance with Islamic values. Students are individuals who are constantly in the process of learning and self-development, both intellectually, emotionally, socially, and spiritually. The Quran also emphasizes that educators must be trustworthy, sincere, patient, forgiving, possess noble character, master knowledge, and be role models for their students. Therefore, the concept of educators and students from a Quranic perspective emphasizes the formation of individuals who are knowledgeable, faithful, pious, and possess noble character as the primary goal of Islamic education.